PEMBERDAYAAN KELUARGA BERBASIS KONEKTIVITAS SOSIAL UNTUK PENCEGAHAN ISOLASI SOSIAL DAN PENINGKATAN KESEHATAN IBU DAN ANAK DI KOTA MAKASSAR - Rusni Mato (INCIDENTAL : Journal Of Community Service and Empowerment, 2026)
This community service program was initiated in response to the high prevalence of perinatal social isolation and maternal depression in Makassar, which may adversely affect maternal and child health outcomes. The program aimed to implement the Family Empowerment–Social Connectedness Maternal and Child Health (FESCMCH) Model through a family-based empowerment approach involving 60 pregnant and postpartum women and their families across three primary health center service areas. The intervention included social isolation screening and counseling, family psychoeducation, structured family meetings, strengthening of maternal classes, and the establishment of peer-support groups. Evaluation was conducted using a pre-post design with the UCLA Loneliness Scale and the Edinburgh Postnatal Depression Scale (EPDS). Results showed a significant reduction in mean social isolation scores from 6.8 to 4.2 and EPDS scores from 10.4 to 6.8 (p<0.001), accompanied by a 34.7% increase in antenatal care attendance and a 78.3% increase in peer-group participation. The FESCMCH Model proved effective in enhancing social connectedness and improving maternal health outcomes.